Two brothers with x linked adrenoleukodystrophy - Islam, QT; Siddiqui, MR; Hossain, A; Hossain, MM; Sina, H; Rahman, MY (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):430-3 The abstract of this article is available on the PubMed website